Analisis Energi Pada Alat Desalinasi Tenaga Surya - Jandri Fan HT Saragi; Eka Putra Dairi Boangmanalu; Angga Bahri Pratama; Franklin Taruyun Hudeardo Sinaga; Al Qadry; Wawan Septiawan Damanik (Rekayasa Material, Manufaktur dan Energi, 2023)
In recent times, many studies have been carried out on desalination systems in areas that have difficulty in obtaining clean water sources. Desalination is a method used to distill salt water or brackish water into clean water using solar power as its energy source. This desalination process is a practical alternative that can be used to offer renewable energy sources that are used to produce clean water. To perform energy analysis, the first law of thermodynamics is used as a basis. This study aims to obtain the results of the amount of energy obtained from the solar desalination system and to determine the factors that greatly affect the amount of energy obtained from the system for evaporating water. The method used in this research is an experiment by testing a solar desalination device for eight days. The results show that the highest thermal energy produced is 8.98 kWh and the lowest is 1.56 kWh, and the factors that influence the amount of thermal energy are the heat transfer coefficient and the amount of distilled water produced by the system.